Gestational Diabetes Mellitus in Pregnancy Increased Erythropoietin Level Affecting Differentiation Potency of Haematopoietic Stem Cell of Umbilical Cord Blood - Mohd Idris, Mohd Razif; Nordin, Fazlina; Mahdy, Zaleha Abdullah; Abd Wahid, S. Fadilah (Frontiers in Medicine, 2021)
Background: The in utero environment has many factors that can support cell differentiation. Cytokines, chemokines and growth factors play big roles in haematopoietic mechanisms. Some diseases like gestational diabetes mellitus (GDM) might affect the environment and haematopoietic stem cell (HSC) quality. The aim of this study is to investigate the adverse effects of GDM on umbilical cord blood (UCB) HSC in terms of differentiation potency including the UCB parameters used for banking and transplantation purposes. Methods: UCB-HSC was collected from 42 GDM and 38 normal pregnancies. UCB-HSC was isolated and further enriched using immuno-magnetic separation beads (MACS). The UCB-HSC were cultured in methylcellulose media to investigate the differentiation potency. The level of erythropoietin (EPO) and insulin in the UCB plasma was measured using enzyme linked immunoassay (ELISA) technique. Result: The UCB parameters; volume, total nucleated count (TNC) and total CD34+ cells were significantly reduced in the GDM group compared to the control group. The number of HSC progenitors’ colonies were significantly reduced in the GDM group except for progenitor BFU-E, which was significantly increased (GDM=94.19 ± 6.21, Control=73.61 ± 2.73, p=0.010). This data was associated with higher EPO level in GDM group. However, the insulin level in the GDM group was comparable to the Control group. Conclusion: Our results suggest that the changes in the in utero environment due to abnormalities during pregnancy such as GDM might affect the differentiation potency of UCB-HSC. These findings can be considered as an additional parameter for the inclusion and exclusion criteria for UCB banking, particularly for mothers with GDM.